Blessed are those who ask the questions : what should we be asking about management, leadership, spirituality, and religion in organizations? - Goosby Smith, J.; Renslow, Erin D. (Contemporary perspectives in management spirituality and religion, 2021)
"Today's organizational environment is characterized by high levels of cross-cultural, cross-national, and cross-religious communication, conflict, collaboration, and commerce. This environment produces myriad encounters between individuals who embrace different ideologies, religions and spiritual practices. As such, unanswered (and even unasked) questions about management, spirituality, and religion abound. This book, seeks to advance our understanding by asking the big questions. Blessed are Those Who Ask the Questions: What Should we be Asking About Management, Spirituality, and Religion in Organizations? is intended to be provocative in nature. Its chapters address novel ways that leadership, organizations, and organizational stakeholders mutually impact each other by their similarities and differences in religious, spiritual, and ideological traditions, cultures, and practices. Interdisciplinary in nature and firmly grounded in scholarly literature, this book identifies and maps out bold new trajectories for advancing the study of management spirituality, and religion (including but going far beyond Western, Christian conceptualizations of religion). Sometimes universal, sometimes quite specific, this volume identifies unexplored, underexplored, or unresolved issues in the field and proposes new streams of research. Diverse conceptual, empirical, theoretical, and critical treatments that honor a variety of inquiry styles and research methods push the boundaries of MSR research"--